2020
DOI: 10.1194/jlr.ra119000423
|View full text |Cite
|
Sign up to set email alerts
|

Role of angiopoietin-like protein 3 in sugar-induced dyslipidemia in rhesus macaques: suppression by fish oil or RNAi

Abstract: Angiopoietin-like protein 3 (ANGPTL3) inhibits lipid clearance and is a promising target for managing cardiovascular disease. Here we investigated the effects of a high-sugar (high-fructose) diet on circulating ANGPTL3 concentrations in rhesus macaques. Plasma ANGPTL3 concentrations increased ∼30% to 40% after 1 and 3 months of a high-fructose diet (both P < 0.001 vs. baseline). During fructose-induced metabolic dysregulation, plasma ANGPTL3 concentrations were positively correlated with circulating indices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 58 publications
1
11
0
Order By: Relevance
“…A recent study by Butler et al explored the effects of suppressing Angptl3 expression with RNAi on lipid metabolism in rhesus macaques 108 . The results revealed that Angptl3 RNAi reduced the plasma levels of TG by 50%, HDL‐C by 52% and LDL‐C by 42.3% 108 . Consistent with this study, a study conducted with RNAi silencing of Angptl3 in mouse liver revealed that Angptl3 deficiency led to lower LDL‐C, TG and HDL‐C 71 .…”
Section: Angptl3‐targeted Therapies In Ascvdsupporting
confidence: 73%
See 3 more Smart Citations
“…A recent study by Butler et al explored the effects of suppressing Angptl3 expression with RNAi on lipid metabolism in rhesus macaques 108 . The results revealed that Angptl3 RNAi reduced the plasma levels of TG by 50%, HDL‐C by 52% and LDL‐C by 42.3% 108 . Consistent with this study, a study conducted with RNAi silencing of Angptl3 in mouse liver revealed that Angptl3 deficiency led to lower LDL‐C, TG and HDL‐C 71 .…”
Section: Angptl3‐targeted Therapies In Ascvdsupporting
confidence: 73%
“…This study provided a potential model strategy with which to treat dyslipidaemic patients. 83 108 The results revealed that Angptl3 RNAi reduced the plasma levels of TG by 50%, HDL-C by 52% and LDL-C by 42.3%. 108 Consistent with this study, a study conducted with RNAi silencing of Angptl3 in mouse liver revealed that Angptl3 deficiency led to lower LDL-C, TG and HDL-C. 71 ARO-ANG3, an RNAi drug designed to silence the expression of Angptl3, showed good tolerability over 16 weeks and resulted in the lowering of LDL-C and TRLs in healthy volunteers.…”
Section: Genome/base Editing and Rna Interference Of Angptl3mentioning
confidence: 96%
See 2 more Smart Citations
“…Plasma insulin and triglycerides, hepatic triglycerides, plasma-free fatty acids, plasma apolipoprotein C3, and total plasma cholesterol were elevated in the AD-fed rats compared to the chow-fed rats and decreased by KHK inhibition, parameters of metabolic disease induced by a diet mirroring the average American diet ( Figure 5 B–G). Decreases in circulating adiponectin have been reported in both humans and non-human primates fed fructose [ [48] , [49] , [50] ]. Surprisingly, adiponectin levels did not differ between chow- and AD-fed rats ( Figure 5 H), perhaps due to lower fructose levels in the AD or differences between species.…”
Section: Resultsmentioning
confidence: 99%